Operárias têxteis: cotidiano e trabalho em São Paulo (1930-1948) - Santos, Juliana Brancaccio dos (2009)
This paper studies the daily and working lives of textile mill women workers between 1930 and 1948, using as a starting point the accounts given by Luiza Brancaccio, Yolanda Helena Lavalle Blancacco and Maria Lavalle Allegranzi. The focus of the study is twofold. Firstly, the author discusses life beyond the mill, describing these women's daily lives in their neighborhoods, their leisure activities, courtship and dating, marriage and the birth of their children. Secondly, the author discusses labor within the São Paulo state textile industry and the large numbers of women workers found in mills. The paper analyses the various types of activities carried out by women workers, the harsh reality of child labor and how these issues were addressed by the social welfare legislation at the time. Finally, the paper looks at the level of respect accorded to these women by society, the roles they were subject to and how they dealt with these societal demands, highlighting that even in those early days news about women's evolution were being published by the press. It is important to underscore that the author does not claim the interviewees' accounts to represent the entire universe of women textile workers in the period. Through these accounts the author wishes to discuss the Brazilian industrialization scene and the situation of women, two topics of great relevance in the history of Brazil. In the early days of our research, these life stories acted as enablers of our task